Integrating Social Media into English Language Learning: How and to What Benefits According to Recent Studies (Universitas Islam Negeri Sunan Ampel Surabaya, 2021)
Social media has become an integral part of life, including in the field of education. This study aimed to explore social media as a teaching and learning tool, its use, and its benefit for students of English as Foreign Language. This study applied library research from George (2008), where the sources of the data were previous studies on the use of social media in the context of English as Foreign Language, published in reputable international journals or accredited national journal ranked SINTA 1, SINTA 2, and SINTA 3, between 2015 to 2020. The review revealed that YouTube, WhatsApp, Facebook, Instagram, and Twitter have been frequently applied as English learning media through various activities that matched the features provided by the respective social media. Their implementations in English learning have been argued to positively impact the students’ language skills, vocabulary, grammar, pronunciation, spelling, motivation, as well as their creative and critical thinking. These results reflect a positive attitude toward social media as an inseparable part of the students’ 21st – century learning contexts. However, more studies need to be conducted to optimize the use of social media for improving students’ English and their 21st-century skills.